Internet marketing Strategy of Commercial Website for NU Skin Distributor - Noer, Muhammad Sherdian Wilandria Syofrinaldy Wilandria Syofrinaldy; Wandebori, Harimukti (Journal of Business and Management, 2014)
Nu Skin Enterprise had been running in Indonesia since early 2005. The company was well-known to many countries in the world especially in Asia. The growth of the company was quite significant and the products were also well-known especially for its anti-aging products. The company used multi-level marketing as its well-suited strategy. However, the disadvantage was that only people who became distributor were the only ones who actively promoted the products. But there were limit they encountered which were distance and time thus could now be covered by todayâ€™s technology, internet, and in order to get the best result, a system and strategy were highly necessary. In Indonesia, Nu Skin was yet known to many people because the products price were categorized as premium in personal care product category, and people awareness toward the products were not that high since there was no commercial advertising and such in Indonesia for its products. Therefore, the strategy that was considered as solution and became topic of this research was about internet advertising and its strategy in creating a website. The objective of this research was mainly to identify people awareness toward the products by making an informative e-commerce website that could be used by distributor to make more effective process in promoting and distributing the products of Nu Skin. The website would be then analyzed according to website and business theory and also interviews result from Nu Skin registered distributors. The analysis would then generate conclusion and recommendation about what kind of website that would be best created and used by Nu Skin distributor. The findings of this research were about website creation and development along with its online advertisement performance. The result was then analyzed to generate internet marketing strategy best suited for the distributors to be implemented in a form of ready-to-use website.Â Keywords: Internet Marketing, STP Analysis, Website Creation and Development